The Influence of Double Jobbing Supra and Political Infrastructure on the Search for Sympathizers in the Election - Hamdi, Aulia; Syahroni, Dwi (International Journal on Advanced Science, Education, and Religion, 2024)
This study aims to analyze the influence of Double Jobbing superstructure and political infrastructure in finding sympathizers in the general election. Double Jobbing, which doubles as a role in various power structures, has great potential to influence political dynamics, particularly in terms of mobilizing sympathizers and mobilizing support. Political superstructure refers to formal institutions, such as the executive, legislature, and political parties, while political infrastructure includes non-formal organizations, such as civil society groups and social networks. This study uses a library research method using a conceptual approach and a case approach, with these methods to explore how it influences both structurally and operationally and the long-term impact of democracy. The results of this study show that the existence of Double Jobbing can increase the effectiveness of sympathetic mobilization, but also has the potential to create conflicts of interest and the emergence of oligarchs. Thus, the influence of Double Jobbing in the political superstructure and infrastructure plays an important role in the process of finding sympathizers, but it is necessary to study the impact on democracy and electoral integrity.